A novel fast-acting sub-perception spinal cord stimulation therapy enables rapid onset of analgesia in patients with chronic pain. (4th March 2021) - Metzger, Clark S.; Hammond, M. Blake; Paz-Solis, Jose F.; Newton, William J.; Thomson, Simon J.; Pei, Yu; Jain, Roshini; Moffitt, Michael; Annecchino, Luca; Doan, Que
ABSTRACT: Background : Treating chronic pain using sub-perception Spinal Cord Stimulation (SCS) does not elicit paresthesia but is associated with long analgesic 'wash-in' (i.e. duration until maximum pain relief) and prolonged assessment of therapy. We describe the attainment of clinically meaningful and rapid-onset analgesic outcomes using a novel sub-perception SCS approach. Methods : This observational case-series evaluated patients implanted with an SCS device for chronic pain, who underwent re-programming utilizing a new methodology in which paresthesia was used to guide sub-perception stimulation field targeting at specific parameters including charge-balanced symmetrical pulses at 90 Hz (termed Fast-Acting Sub-Perception Therapy, FAST). Pain scores (NRS) were collected as reported per standard-of-care from patient charts. Results : Mean overall pain score at baseline was 8.4 ± 0.2 (n = 41). After activation of FAST, a 7.1-point reduction in overall pain score was (1.3 ± 0.2, p < 0.0001) reported within 11.2 ± 1.9 minutes (n = 34). This decrease in pain score was sustained out to 3-month (1.6 ± 0.3, n = 26) and 6-month follow-up (1.7 ± 0.4, n = 18). At last follow up (mean = 223 ± 132 days), a pain score of 1.6 ± 0.3, n = 30 was determined. Conclusions : After FAST implementation, a profound analgesic response, requiring substantially less energy than conventional sub-perception methodologies, was observed. This rapid analgesic onset achieved with the novel FAST technique suggests the potential for an alternative mechanism of action(s) of sub-perception SCS.